Autoimmune Hepatitis Associated With Turmeric Consumption. Issue 3 (16th March 2020) - Lee, Brian S.; Bhatia, Taruna; Chaya, Charles T.; Wen, Robert; Taira, Mark T.; Lim, Brian S.
ABSTRACT: Turmeric is a popular herbal dietary supplement that has been considered safe and even shown to have hepatoprotective properties. In the recent times, however, there have been a few case reports of turmeric-induced liver injury. We report a 55-year-old woman with chronic turmeric consumption whose initial diagnosis was acute autoimmune hepatitis. She declined steroid treatment, and hence, we recommended discontinuing her long-term turmeric usage. A month after discontinuation, her liver function returned to normal. This case demonstrates the importance of recognizing the potential adverse effects of herbal dietary supplement.